The influence of product type on online trust - Hassanein, Khaled; Head, Milena M.; McMaster eBusiness Research Centre (MeRC) (My University, 2004)
Trust is a critical factor in establishing a successful relationship between consumers and vendors. This paper investigates the impact of the product type being sought on consumers' trust within an online environment. An empirical study involving 227 online shoppers was conducted to develop and validate a structural equation model for online trust incorporating the factors of perceived usefulness, perceived ease of use and enjoyment as representative variables of a consumer's experience within a company's Web site. Results from this study indicate significant variations in the experience and trust levels of tangible versus intangible product shoppers.
18 leaves : ; Includes bibliographical references (leaves 13-18). ; "March 2004".
Keywords: Trust; Online shopping; Product type; Perceived enjoyment; Perceived ease of use; Perceived usefulness; Electronic commerce; Consumer confidence; Product management